IMPACT OF TRANSFERRING LIGHT BUSSES TO BRT ROUTE ON TRAFFIC CONGESTION, MOBILITY, AND SAFETY AT SWEILEH INTERSECTION IN AMMAN - Nsour, Khaled; Iskandarani, Mahmoud (Journal of Applied Engineering Science, 2025)
This research aims to assess the impact of light buses on mobility and time delays. Extended wait times and unfavourable environmental factors lead to traffic jams and negative economic impacts. One suggestion is to relocate these minibuses to the bus rapid transit (BRT) lane. Three crossroads that are connected by a corridor were included in the analysis. The crossroads under consideration are the University of Jordan intersection, the Sweileh intersection, and the intersection of external patrols. Vissim simulation software is used for the evaluation and analysis, using data from detectors data at crossings. As a result of shorter wait times and shorter lines, both the simulation and the collected findings demonstrated an overall improvement in mobility. The environment would benefit from such an upgrade. The inclusion of light buses does, nonetheless, cause a little delay on the BRT lane; however, this is offset by an overall improvement in the mobility of all traffic at each crossing. Improved quantitative assessment of the dynamic traffic at each crossing was made possible based on simulation. The results generated by this study demonstrated intricate traffic interaction models (involving Sweileh, outside patrols, and the University of Jordan), which might be applied during the design phase of upcoming construction projects near these crossings.
Keywords: intersection, bus rapid transit, light busses, mathematical modelling, simulation, vissim